Innovative Leadership of Madrasah Aliyah Principals in Enhancing Educational Quality in Pidie, Aceh Province - Abdullah; Idris, Jamaluddin; Silahuddin (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2024)
This study explores the innovative leadership practices of Islamic senior high school (known as Madrasah Aliyah) principals in Pidie Regency, Aceh, aimed at enhancing educational quality. It addresses the research gap regarding innovative leadership in madrasahs, particularly in Aceh—a post-conflict region with strong cultural and religious values. The study draws on Transformational Leadership and Adaptive Leadership theories to frame its analysis. Using a qualitative case study approach, data were collected from 32 informants, including principals, teachers, students, and school committee members, from eight purposively selected State Madrasah Aliyahs. Data collection methods included direct observation, in-depth interviews, and document analysis. The findings identify five key components of innovative leadership: strategic vision, stakeholder orientation, collaboration, trust-building, and open communication. Practical strategies, such as technology-based learning and community engagement, were implemented to address challenges in student performance while preserving cultural and religious identity. These results underscore the pivotal role of innovative leadership in balancing tradition and modernity, offering actionable recommendations for principals and policymakers to develop adaptive leadership strategies in similar educational contexts. Abstrak: Penelitian ini bertujuan untuk mengeksplorasi perilaku kepemimpinan inovatif kepala Madrasah Aliyah di Kabupaten Pidie, Aceh, dalam meningkatkan kualitas pendidikan. Studi ini mengisi kesenjangan penelitian terkait terbatasnya kajian tentang kepemimpinan inovatif di madrasah, khususnya dalam konteks Aceh sebagai wilayah pasca-konflik dengan nilai budaya dan agama yang kuat. Dengan menggunakan teori Transformational Leadership dan Adaptive Leadership, penelitian kualitatif dengan metode studi kasus, penelitian ini melibatkan 32 informan dari delapan Madrasah Aliyah Negeri yang dipilih secara purposive. Informan terdiri atas kepala madrasah, guru, siswa, dan anggota komite sekolah. Data dikumpulkan melalui observasi langsung, wawancara mendalam, dan analisis dokumen. Hasil penelitian mengidentifikasi lima aspek utama kepemimpinan inovatif: visi strategis, orientasi pada pemangku kepentingan, kolaborasi, pembangunan kepercayaan, dan komunikasi terbuka. Strategi praktis seperti pembelajaran berbasis teknologi serta keterlibatan komunitas diterapkan untuk mengatasi tantangan rendahnya hasil belajar sambil mempertahankan identitas budaya dan religius. Hasil ini menegaskan pentingnya kepemimpinan inovatif dalam menyeimbangkan tradisi dan modernitas, sekaligus menawarkan rekomendasi strategis bagi kepala madrasah dan pembuat kebijakan untuk mengembangkan kepemimpinan adaptif dalam konteks pendidikan serupa.